Diagnostic performance of neuroimaging in suspected idiopathic intracranial hypertension. (February 2022) - Wang, Michael T.M.; Prime, Zak J.; Xu, William; McKelvie, James; Papchenko, Taras; Padungkiatsagul, Tanyatuth; Moss, Heather E.; Danesh-Meyer, Helen V.
Highlights: Multicentre retrospective analysis of 204 patients with suspected papilloedema. 156 participants fulfilled the Friedman criteria for primary pseudotumor cerebri. MRI/MRV signs exhibited a sensitivity of 74.8% and specificity of 94.7% for IIH. CT/CTV signs exhibited a sensitivity of 61.0% and specificity of 100.0% for IIH. Abstract: The diagnostic utility of neuroradiologic signs associated with idiopathic intracranial hypertension (IIH) for the evaluation of patients presenting with papilloedema remains yet to be elucidated. This multicentre retrospective cohort study assessed consecutive patients presenting with suspected papilloedema to Auckland District Health Board (NZ) and Stanford University Medical Centre (US), between 2005 and 2019, undergoing magnetic resonance imaging and venography (MRI/MRV) or computed tomography and venography (CT/CTV) prior to lumbar puncture assessment for diagnostic suspicion of IIH. Data were collected regarding demographic, clinical, radiologic, and lumbar puncture parameters, and the diagnosis of IIH was determined according to the Friedman criteria for primary pseudotumor cerebri syndrome. A total of 204 participants (174 females; mean ± SD age 29.9 ± 12.2 years) were included, and 156 (76.5%) participants fulfilled the diagnostic criteria for IIH. The presence of any IIH-associated radiologic sign on MRI/MRV demonstrated a sensitivity (95% CI) of 74.8% (65.8%–82.0%) and specificity (95% CI) of 94.7% (82.7%–98.5%), while radiologic signs on CT/CTV exhibited a sensitivity (95% CI) of 61.0% (49.9%–71.2%) and specificity (95% CI) of 100.0% (83.2%–100.0%). In summary, the modest sensitivities of radiologic signs of IIH would support the routine use of lumbar puncture assessment following neuroimaging to secure the diagnosis. However, the high specificities might lend limited support for the judicious deferment of lumbar puncture assessment among typical IIH demographic patients who consent to the inherent small risk of missed pathology, which has been proposed by some clinicians.